1974
DOI: 10.1037/h0037446
|View full text |Cite
|
Sign up to set email alerts
|

Alphabet and attraction: An unobtrusive measure of the effect of propinquity in a field setting.

Abstract: The relationship between propinquity and interpersonal attraction was studied in a field setting. Place in alphabetical order was used as an unobtrusive (and conservative) measure of propinquity. The effect of proximity on friendship choice among 44 Maryland State Police trainees was found to be stronger than the effects of a wide variety of other characteristics that have been identified in the literature as determinants of interpersonal attraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 9 publications
1
54
0
1
Order By: Relevance
“…Research has revealed the power of physical closeness in determining social ties (Festinger, Schachter, & Back, 1950;Segal, 1974). One reason why close physical distance and frequent encounters may promote social connection is because each occasion in which a person is encountered presents the opportunity for that partner to be perceived as instrumental to one's goals (and for one to be instrumental to that person's goals).…”
Section: Relationship Initiation and Evaluationmentioning
confidence: 99%
“…Research has revealed the power of physical closeness in determining social ties (Festinger, Schachter, & Back, 1950;Segal, 1974). One reason why close physical distance and frequent encounters may promote social connection is because each occasion in which a person is encountered presents the opportunity for that partner to be perceived as instrumental to one's goals (and for one to be instrumental to that person's goals).…”
Section: Relationship Initiation and Evaluationmentioning
confidence: 99%
“…Echoing Segal's (1974) work on propinquity, Satoshi revealed he developed a close circle of friends amongst the people who happened to sit near to him during inductions and the initial classes of his first few days at university, and it was with these people that he spent nearly all of his time with for the next couple of years. He explained how he and his fellow first years tended to be assigned seats according to their student number and thus cliques of students regularly placed in adjacent seats soon developed.…”
Section: Silence and Embarrassmentmentioning
confidence: 99%
“…Many studies have shown that proximity predicts liking (e.g., Back, Schmukle, & Egloff, 2008;Festinger, Schachter, & Back, 1950;Nahemow & Lawton, 1975;Segal, 1974). People tend to encounter others in close proximity more often; hence, they become more familiar.…”
mentioning
confidence: 99%